Republic of Mozambique : Poverty Reduction Strategy Paper; Annual Progress Report; Review of the Economic and Social Plan for 2007. (IMF Staff Country Reports; Country Report ;, 2008)
This Annual Progress Report reviews the Poverty Reduction Strategy Paper and Economic and Social Plan for 2007 for Mozambique. The report presents the new simplified structure adopted in the Review of the First Half of 2007. In the international context, the evolution of the international economy is presented, which allows a visualization of the international economic conditions in which the country has implemented its economic and social policy. The activities of the environment and the science and technology sectors are also described.